Effects of Quarter-Wavelength Resonators on Air In-take Module of an ICE Engine Using 1-Dimensional Method - Dahlan, Afiq Aiman; Muhamad Said, Mohd Farid; Khairuddin, Muhammad Hariz; Kadir, Khairuldean Abd; Yusoff, Mohd Anuar Mohd (International Journal of Engineering and Technology, 2018)
Air intake module has a main purpose in an engine environment that is to provide sufficient and clean air to the engine. The module is a very critical function which affects the engine performance from pressure restrictions and acoustic performance. A good AIM reduces the engine noise to prevent it from contributing noise to the passenger cabin. To design a good AIM, several tests must be done to optimize the design for good performance notwithstanding the noise propagation. This paper focused on the One-Dimensional (1-D) approach to study the effects of quarter-wavelength resonators on the AIM of an ICE engine. AIM is rather a complex module as the air flows from snorkel to the engine, but at the same time the noise from the engine operations propagates on the different direction. AIM operates at rather wide frequency range where suitable design of ducts, resonators and volume of air box is important so that the system meets the targeted sound pressure level (SPL). Resonator is commonly added to ducting system to attenuate noise at desired frequency. Multiple resonators may be added to attenuate engine noise at wider broad band frequencies. In this paper, the effects of removing quarter-wavelength resonator on the original AIM designs of an ICE engine. The 1-D model is built in commercial simulation tool named GT-Power to measure the transfer function.